2023
DOI: 10.1021/acs.langmuir.2c02266
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Pickering Double Emulsions by in Situ Particle Surface Modification

Abstract: Fundamental studies on the formation and stability of Pickering double emulsions are crucial for their industrial applications. Available methods of double emulsion preparation involve multiple tedious steps and can formulate a particular type of double emulsion, that is, water-in-oil-in-water (w/o/w) or oil-in-water-in-oil (o/w/o). In this work, we proposed a simple single-step in situ surface modification method to stabilize different types of double emulsions using hematite and silica particle systems which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The arrangement of particles on the surface of the inner oil drops and the surface of larger water drops in the O/W/O emulsions were visualized by SEM. The emulsion samples were first freeze-dried (Christ, Alpha 1–2 LDplus, Germany), sputter-coated with gold for 20 s, and finally observed under a scanning electron microscope …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The arrangement of particles on the surface of the inner oil drops and the surface of larger water drops in the O/W/O emulsions were visualized by SEM. The emulsion samples were first freeze-dried (Christ, Alpha 1–2 LDplus, Germany), sputter-coated with gold for 20 s, and finally observed under a scanning electron microscope …”
Section: Methodsmentioning
confidence: 99%
“…The emulsion samples were first freeze-dried (Christ, Alpha 1−2 LDplus, Germany), sputter-coated with gold for 20 s, and finally observed under a scanning electron microscope. 30…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its ease of use and effectiveness, one-step emulsification has recently attracted increasing attention for preparing Pickering double emulsions in situations near phase inversion . Typically, this emulsification uses a single particle stabilizer, mainly including inorganic particles and synthetic polymer particles (micelles, microgel, and latex), with either intermediate hydrophobicity or a distribution of wettability. For example, Bai et al prepared O/W/O Pickering double emulsions using palmitoyl chloride to increase the hydrophobicity of diatomite particles . A W/O/W Pickering double emulsion with amphiphilic Janus particles that have a hydrophilic area rich in acrylic acid and a hydrophobic area rich in styrene was described by Lee et al Nonomura et al found that silicone particles shaped like a bowl with varying wettability caused by contact angle hysteresis due to solvent entrapment can stabilize Pickering double emulsions .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple Pickering emulsions that are stabilized by colloidal particles are emerging as a promising strategy for constructing multicompartmentalized microreactors. , Because the high adsorption energy of colloidal particles at the droplet surface renders them more stable than usual surfactant-based soft material systems . Apart from the stability, fabrication of Pickering emulsions has a broad range of liquids for choice since any two immiscible liquids can in principle form Pickering emulsions .…”
Section: Introductionmentioning
confidence: 99%